2019
DOI: 10.18203/2394-6040.ijcmph20195499
|View full text |Cite
|
Sign up to set email alerts
|

Organising a medical camp in a community: are there lessons to be learned?

Abstract: Part of curriculum requirements for year 3 medical students at AIMST University is to organise a medical camp at end of their community medicine posting. The purpose was two-fold: to orientate medical students towards health needs of the people at primary care level and to bring health awareness to communities that have less access to basic health care services. Annually, seven such camps are held. Our aim was to assess the lessons learned by medical students in this activity and we based our findings from a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Since most of the time medical services provided during these camps are free, studies have shown that such healthcare camps ensure equity in accessing health care services including the availability of health education to the community [19][20][21][22] . Medical students can do this by organizing, implementing, or participating in such events through their local students' professional associations like the International Federation of Medical Students' Association (IFMSA) or their medical schools [23,24] . Through this, they will bring healthy transformation in the community while at the same time enhancing their medical knowledge and skills as part of learning.…”
Section: Role Of Medical Students In Community Lifestyle Transformationmentioning
confidence: 99%
“…Since most of the time medical services provided during these camps are free, studies have shown that such healthcare camps ensure equity in accessing health care services including the availability of health education to the community [19][20][21][22] . Medical students can do this by organizing, implementing, or participating in such events through their local students' professional associations like the International Federation of Medical Students' Association (IFMSA) or their medical schools [23,24] . Through this, they will bring healthy transformation in the community while at the same time enhancing their medical knowledge and skills as part of learning.…”
Section: Role Of Medical Students In Community Lifestyle Transformationmentioning
confidence: 99%